2018
DOI: 10.1155/2018/9050812
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Ten Common QRS Detectors on Different ECG Application Cases

Abstract: A systematical evaluation work was performed on ten widely used and high-efficient QRS detection algorithms in this study, aiming at verifying their performances and usefulness in different application situations. Four experiments were carried on six internationally recognized databases. Firstly, in the test of high-quality ECG database versus low-quality ECG database, for high signal quality database, all ten QRS detection algorithms had very high detection accuracy (F1 >99%), whereas the F1 results decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 35 publications
0
71
1
Order By: Relevance
“…A preprocessing step was brought in for denoising, mainly including power frequency interference, baseline drift, myoelectricity interference, motion artifacts, and electrode contact noise [24]. The annotation of QRS complex is the most important task, where an algorithm based on the Pan and Tompkins has a preferable performance [23,25,26]. Features are used to represent patterns with minima loss of important information.…”
Section: Ecg Cloud Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…A preprocessing step was brought in for denoising, mainly including power frequency interference, baseline drift, myoelectricity interference, motion artifacts, and electrode contact noise [24]. The annotation of QRS complex is the most important task, where an algorithm based on the Pan and Tompkins has a preferable performance [23,25,26]. Features are used to represent patterns with minima loss of important information.…”
Section: Ecg Cloud Platformmentioning
confidence: 99%
“…The most commonly used databases on published researches for arrhythmia are the MIT-BIH Arrhythmia Database, QT Database, CSE Database, and AHA Database [20]. Although classical they are, the characteristic of non-wearable makes them not perfect for dynamic automatic analysis algorithm designing [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The six detectors were separately named as Hamilton-median algorithm [18], sixth-power algorithm [19], U3 transform algorithm (U3 algorithm) [20], difference operation algorithm (DOM algorithm) [21], 'jqrs' algorithm [22]- [24], optimized knowledge based algorithm (OKB algorithm) [25] in this paper. Though they were built on different basic theories, they all had high efficiencies and could be executed in nearly real-time processing on the mobile devices [26].…”
Section: ) Heart Rate Annotationsmentioning
confidence: 99%
“…A recent study demonstrated that even when using state-of-the-art QRS detectors, an 80% or higher accuracy of QRS detection is not achieved. By contrast, these methods can easily obtain a 99% accuracy using conventional ECG databases such as the PhysioNet/MIT Arrythmias database [ 37 ]. Potential detection errors from the automatic analysis of dynamic ECGs also bring abnormal RR intervals, i.e., RR intervals lasting for too much or too little time.…”
Section: Introductionmentioning
confidence: 99%